2021
DOI: 10.1371/journal.ppat.1009402
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus evolution in immunodeficient mice reveals potentiated pathogenicity via a single nucleotide change in the viral capsid

Abstract: Interferons (IFNs) are key controllers of viral replication, with intact IFN responses suppressing virus growth and spread. Using the murine norovirus (MNoV) system, we show that IFNs exert selective pressure to limit the pathogenic evolutionary potential of this enteric virus. In animals lacking type I IFN signaling, the nonlethal MNoV strain CR6 rapidly acquired enhanced virulence via conversion of a single nucleotide. This nucleotide change resulted in amino acid substitution F514I in the viral capsid, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…1b,c and Extended Data Fig. 1a,b ), MNV-3, MNV-4 and the less-well-characterized WU23 murine norovirus strains persistently infect the proximal colon and shed into feces for weeks 22 25 . We inoculated mice with these strains and found that all were also persistently shed in saliva for at least 3 weeks after inoculation, with titres approximately 10 3 -fold higher than input (6 hpi) (Fig.…”
Section: Enteric Viruses Are Transmitted Through Salivamentioning
confidence: 97%
“…1b,c and Extended Data Fig. 1a,b ), MNV-3, MNV-4 and the less-well-characterized WU23 murine norovirus strains persistently infect the proximal colon and shed into feces for weeks 22 25 . We inoculated mice with these strains and found that all were also persistently shed in saliva for at least 3 weeks after inoculation, with titres approximately 10 3 -fold higher than input (6 hpi) (Fig.…”
Section: Enteric Viruses Are Transmitted Through Salivamentioning
confidence: 97%
“…Transmission electron microscopy images of MGDG-treated HSV-2 particles showed that MGDG treatment might cause morphological changes in not only the envelope but also the capsids of the virus particles, as judged from the reduction of their diameter. The MNV capsid plays a crucial role in binding to its receptor on host cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was obtained from Dr. Tohya, Nihon University, Japan. This strain has been widely used in investigating the receptor for MNV [35] and tests for virucidal and antiviral substances [16,36]. The MNV S7-PP3 strain was propagated in RAW 264.7 cells (ATCC TIB-71).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…There are data to support a cellular tropism for intestinal epithelial [43][44][45] and/or immune cells [46][47][48][49] for HNoV and MNoV that may be strain-specific. Recent insights, which will be subsequently defined, have demonstrated crucial aspects of MNoV-IFN interactions in regulating virulence as well as cellular tropism of this prominent pathogen [50][51][52].…”
Section: Trends In Immunologymentioning
confidence: 99%